New directions of bitter lupine seed utilization - Gulewicz, Krzysztof (Committee on Biotechnology PAS, 1989)
During studies on the complex utilization of protein and other bitter lupine seed components, conducted in the Institute of Bioorganic Chemistry, Polish Academy of Sciences in Poznań, a new method of removing of antinutritional factors (alkaloids, oligosaccharides of raffinose family) was elaborated. It consists in extraction of properly prepared lupine seeds with aqueous solutions of alcohols. As a result of this process, a fully valuable high-protein fodder and an extract containing other natural products (alkaloids, free amino acids, peptides, sugars, organic acids, etc.) were obtained. It was also clearly showed that lupine extracts could find potential application in national economy as natural plant protection means and also as a crop increasing factors.
Keywords: biotechnology